Animation Lab for Kids : Fun Projects for Visual Storytelling and Making Art Move - From cartooning and flip books to claymation and stop motion movie making. - Bellmont, Laura (LAB (Series), 2016)
In Animation Lab for Kids, artists, teachers, and authors Laura Bellmont and Emily Brink present exciting, fun, hands-on projects that teach kids a range of animation techniques.